Criticism of Jacques Derrida's Deconstruction Application to Al-Qur'an Verses - Fajriyaturrohmah, Fajriyaturrohmah; Labib, Muhammad Alfreda Daib Insan (Universitas Islam Negeri Sunan Ampel Surabaya, 2023)
Derrida's deconstruction is one of the contemporary ideas in the world of philosophy of language. This concept seeks to completely overhaul the meaning of a text so that the reader is not trapped in a meaning that has been constructed for a long time. Studies related to Deconstruction are interesting to be studied from various aspects. In this article, the method used is descriptive analysis and the type of research is literature research. While the problems studied are the definition, background, urgency, and working concept of Deconstruction. In addition, the core of this paper discusses criticism of the application of Deconstruction to the Qur'anic verse contained in one of the articles in the Journal. The results of the study show that Derrida's Deconstruction is a new breakthrough in the world of linguistic philosophy that frees the reader to interpret what is in his mind from the results of reading the text. Other results show that the Deconstruction of Derrida is not suitable for use in the application of Qur'anic verses.